Delivery Timing and Associated Outcomes in Pregnancies With Maternal Congenital Heart Disease at Term - Thalia Mok; Allison Woods; Adam Small; Mary M. Canobbio; Megha D. Tandel; Lorna Kwan; Gentian Lluri; Leigh Reardon; Jamil Aboulhosn; Jeannette Lin; Yalda Afshar (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Current recommendations for delivery timing of pregnant persons with congenital heart disease (CHD) are based on expert opinion. Justification for early‐term birth is based on the theoretical concern of increased cardiovascular stress. The objective was to evaluate whether early‐term birth with maternal CHD is associated with lower adverse maternal or neonatal outcomes. Methods and Results This is a retrospective cohort study of pregnant persons with CHD who delivered a singleton after 37 0/7 weeks gestation at a quaternary care center with a multidisciplinary cardio‐obstetrics care team between 2013 and 2021. Patients were categorized as early‐term (37 0/7 to 38 6/7 weeks) or full‐term (≥39 0/7) births and compared. Multivariable logistic regression was conducted to calculate the adjusted odds ratio for the primary outcomes. The primary outcomes were composite adverse cardiovascular, maternal obstetric, and adverse neonatal outcome. Of 110 pregnancies delivering at term, 55 delivered early‐term and 55 delivered full‐term. Development of adverse cardiovascular and maternal obstetric outcome was not significantly different by delivery timing. The rate of composite adverse neonatal outcomes was significantly higher in early‐term births (36% versus 5%, P<0.01). After adjusting for confounding variables, early‐term birth remained associated with a significantly increased risk of adverse neonatal outcomes (adjusted odds ratio 11.55 [95% CI, 2.59–51.58]). Conclusions Early‐term birth for pregnancies with maternal CHD was associated with an increased risk of adverse neonatal outcomes, without an accompanying decreased rate in adverse cardiovascular or obstetric outcomes. In the absence of maternal or fetal indications for early birth, induction of labor before 39 weeks for pregnancies with maternal CHD should be reserved for routine obstetrical indications.